Shadow Theatre as a Performative Art for the Development of Uninhibited Corporal Expression and Group Cohesion in Sixth-Grade Students of Primary Education - Bravo-Fuentes, Paloma (Harmonia: Journal of Arts Research and Education, 2023)
Shadow theatre is an educational resource based on the use of silhouettes and the body as a means of communication. It allows the incorporation of music and sound effects that help students discover movement possibilities in the stage space. It also encourages collaborative work through the creation of groups. Therefore, the aim of this research is the incorporation of shadow theatre as a performance art for the promotion of uninhibited corporal expression and group cohesion. An action-research methodology is used to define a didactic proposal that incorporates shadow theatre in the field of music education at primary school. The learning situation is carried out in two public schools in the province of Malaga, with a sample of 213 students. The results indicate that shadow theatre effectively improved pupils’ body expression and group cohesion. Some students had initial difficulties, but thanks to the anonymity provided by this resource, fear of ridicule was reduced. It is proposed to compare this resource with theatre in order to define whether the method of incorporating the shadow is really effective.